“love : necessity : anti-fa”: Hostile Environments and Necropolitics in Nat Raha’s Of Sirens, Body & Faultlines and Jay Bernard’s Surge - Juha Virtanen (Anglica. An International Journal of English Studies, 2023)
The UK’s legislation on immigration in the 2010s has been defined by a hostile environment. This essay traces the ways in which two poets in the UK have responded to, and intervened in, this violent political climate. Through a close examination of Nat Raha’s Of Sirens, Body & Faultlines and Jay Bernard’s Surge, the essay demonstrates how both poets understand the present hostile environment in a wider historical context, and how they consequently make possible a new understanding of our contemporary moment, as well as possible pathways towards resisting the UK’s necropolitical immigration policies.